Turkish written documents as sources of information on the history of Ukraine of the second half of the 16th century - Туранли Ф. (Видавничо-поліграфічний центр "Київський університет", 2017)
The article examines of archival documents containing data on the history of Ukraine relating the development period of the Ukrainian Cossackdom, particularly on the military activities of Hetman Dmytro Vyshnevetsky. The policy of the High Porte aimed at preventing combat operations of the Ukrainian Cossacks against the High Porte and Crimean Khanate in the Azov Sea Area. There has been analysed the political situation set up in the relationships between the Ottoman Empire, Muskovite Czardom and Poland in the second half of the 16th century. The point of the international trade routes and the issue of providing safety for such a communication have been touched on. The methodology of studying the Turkish Ottoman written sources on the above said theme is the objective interpretation of the texts of the sources, which requires application of a coresponding method.

У статті досліджуються архівні документи, які містять відомості з історії України періоду розвитку українського козацтва, зокрема про військову діяльність гетьмана Дмитра Вишневецького. Розглядається політика Високої Порти, спрямована на запобігання бойових дій з боку українських козаків проти Високої Порти та Кримського ханства у Приазов'ї. Проаналізовано політичну ситуацію, яка склалася у відносинах між Османською імперією, Московським царством і Польщею в другій половині XVI ст. Зазначається про міжнародні торгівельні шляхи та питання забезпечення безпеки такої комунікації. Проблема методології дослідження османсько-турецьких писемних джерел із зазначеної теми полягає в об'єктивній інтерпретації текстів досліджуваних джерел, що потребує застосування відповідного методу.
Турецькі рукописні документи як джерела інформації з історії України другої половини XVI ст.
Keywords: methodology; a Turkish Ottoman written source; Historiography; the Ukrainian Cossackdom; Dmytro Vyshnevetsky; Azov; the Crimean Khanate; the High Porte; trading; методологія; османсько-турецьке писемне джерело; історіографія; українське козацтво; Дмитро Вишневецький; Азов; Кримське ханство; Висока Порта; торгівля